2017
DOI: 10.1002/cncy.21841
|View full text |Cite
|
Sign up to set email alerts
|

Cytologic characteristics of circulating epithelioid cells in pancreatic disease

Abstract: Background Circulating epithelioid cells (CECs), also known as circulating tumor/cancer/epithelial/non-hematologic cells, are a prognostic factor in various malignancies that can be isolated via various protocols. We analyzed the cytomorphologic characteristics of CECs isolated by size in a cohort of patients with benign and malignant pancreatic diseases to determine if cytomorphological features could predict CEC origin. Methods Blood samples were collected from 9 healthy controls and 171 patients with panc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 34 publications
2
35
0
Order By: Relevance
“…It is possible that other researchers have found megakaryocytes while looking for CTCs but have not recognised them. Images of megakaryocyte‐like cells have been published in at least one previous paper on CTCs . In the current study, we also found that megakaryocytes were more common in patients with carcinoma than in healthy volunteers.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…It is possible that other researchers have found megakaryocytes while looking for CTCs but have not recognised them. Images of megakaryocyte‐like cells have been published in at least one previous paper on CTCs . In the current study, we also found that megakaryocytes were more common in patients with carcinoma than in healthy volunteers.…”
Section: Discussionsupporting
confidence: 80%
“…one previous paper on CTCs. 13 In the current study, we also found that megakaryocytes were more common in patients with carcinoma than in healthy volunteers. Many of the megakaryocytes appeared to have lost their cytoplasm.…”
Section: Images Of Megakaryocyte-like Cells Have Been Published In Atsupporting
confidence: 69%
See 1 more Smart Citation
“…However, this has to be taken with a grain of salt, since this cannot be assigned to all tumor entities. For example, screening for pancreatic ductal adenocarcinoma (PDAC) by liquid biopsy has low specificity due to the fact that other non-malignant diseases of the pancreas like chronic pancreatitis can lead to high rates of false positive epithelial cell numbers in the blood [8,9].…”
Section: Ctcs As Screening Toolmentioning
confidence: 99%
“…Also one of the PCR-based studies report a rate of 11% in cases with benign pancreatic disease, while reporting only one positive case in 20 healthy controls (30). In addition, there is one report disclosing the presence of epithelal cells in the bloodstream of patients with benign pancreatic disease (31). These cells could potentially enter the bone marrow via the bloodstream and could thereby be detected in BM-samples as well.…”
Section: Icc-positive Cases In Benign Pancreatic Diseasementioning
confidence: 99%